1978
DOI: 10.1007/bf00154931
|View full text |Cite
|
Sign up to set email alerts
|

Motions in solar magnetic tubes

Abstract: The method of Giovanelli and Brown (1977) has been used with a variety of spectral lines to study oscillating longitudinal gas velocities inside solar magnetic elements. Oscillations have been found inside all elements observed, the amplitudes increasing with height from typically +0.27kms -I in Fe 15166 ~ (a line of low origin) to + 0.75 km s-1 in Ha. Simultaneous observations in pairs of lines show that a given disturbance occurs later with height, so that disturbances propagate outwards. The period is typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 13 publications
4
10
0
Order By: Relevance
“…Although we have verified in §3.1 that RD has not contaminated (i.e., introduced artifacts in) the quiet-Sun t ph confirming our identification in §2.2 that τ R is nearly constant over the height ranges considered, we still need to address if the nearly vertical network flux tubes present suitable physical conditions so different from the quiet-Sun that either (i) artifacts of height dependent RD, or (ii) a large reduction in acoustic cut-off due to strong RD (Giovanelli et al 1978;Roberts 1983; Centeno et al 2006; Khomenko et al 2008) could be responsible for the above 2 -4 mHz propogation.…”
Section: Phase Travel-timessupporting
confidence: 63%
See 1 more Smart Citation
“…Although we have verified in §3.1 that RD has not contaminated (i.e., introduced artifacts in) the quiet-Sun t ph confirming our identification in §2.2 that τ R is nearly constant over the height ranges considered, we still need to address if the nearly vertical network flux tubes present suitable physical conditions so different from the quiet-Sun that either (i) artifacts of height dependent RD, or (ii) a large reduction in acoustic cut-off due to strong RD (Giovanelli et al 1978;Roberts 1983; Centeno et al 2006; Khomenko et al 2008) could be responsible for the above 2 -4 mHz propogation.…”
Section: Phase Travel-timessupporting
confidence: 63%
“…Although a complete physical model capturing all the features in I − V spectra is still lacking, existing literature includes successful models based on the correlated noise background (turbulent convection that excites the oscillations) to explain the interridge background and modal asymmetries in the I and V power spectra (Nigam & Kosovichev 1999;Skartlien & Rast 2000) while other models that include non-adiabaticity due to radiative damping claim better match with observations (Severino et al 2013). τ R << τ S , apart from radiatively damping the already propagating waves (Souffrin 1972;Newington & Cally 2011) RD can also cause the evanescent waves to propagate by significantly lowering the acoustic cut-off frequency (Giovanelli et al 1978;Roberts 1983Roberts , 2006Centeno et al 2006;Khomenko et al 2008) -we discuss this further in §3.2.1 and §4 in relation to the results obtained in this work.…”
Section: Phase (Travel-times) and Coherence Spectrasupporting
confidence: 51%
“…As is immediately obvious in Figure Ic, the velocity field in the magnetic fine structure is dominated by the 5-min oscillations. A similar behaviour was found before already by Giovanelli et al (1978), Wiehr (1985), Fleck and Deubner (1991) and Fleck (1991). The RMS of the velocity fluctuations is about 220 m/s only.…”
Section: Resultssupporting
confidence: 89%
“…They find evidence for continuous (or intermittent) heating. Giovanelli et al (1978) observed motions in solar magnetic tubes. According to them the disturbance velocities never exceed about 0.1 of the velocity of sound, Withbroe and Noyes (1977) Transition layer pressure ( dyn cm-2): Coronal fluxes (era cm -2 s--l): conductive 2 9 105 6 9 104 radiative 105 104 wind < 5 9 104 7-105 totM 3.105 8 -105 Chromospheric flux (era cm -2 s-l): total 4.106 4.106…”
Section: Heating By Magnetic Flux Emergencementioning
confidence: 99%